(untitled) (Current Problems in Rail Vehicles, 2021)
This contribution deals with potential benefits of semi-active dampers for a railway vehicle. With the help of vertical or lateral secondary dampers, it is possible to significantly reduce a vibration level of the vehicle body and thus increase passengers’ comfort. By controlling the yaw dampers, it is possible to improve running stability and reduce wear in the wheel/rail contact, whether using slow adaptive control or fully semi-active control. The benefit of adaptive mode has been verified on a real vehicle with a magnetorheological damper developed within the Czech Ministry of Industry and Trade project by the company Strojírna Oslavany, spol. s r.o. in cooperation with the Brno University of Technology. This paper then describes the simulation verification of the benefits of fully semi-active control of a developed yaw damper with a short time response. The simulation results show that the application of a suitable algorithm allows to reach smooth running of the investigated vehicle at higher speed in a straight track and has a potential to reduce the level of wear in wheel/rail contact.